Georgia Architectural and Historic Properties Survey of 706 Jackson St., Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 706 Jackson St., Valdosta, Ga. One story house of rectangular plan with hipped tin roof. Exposed rafters. Brick square posts. Shiplap siding. Interior chimney. Double hung sash windows with 2/2 lights. Shutters. Large plate glass windows. Fair condition. Date of Construction: App. 1915-1920. Typical vernacular house in a district of similar houses built in the early 1900's. - Has significance as part of a potential N.R. district.
1 electronic record and derivatives. 1 PDF. 3 scans. 81.4 MB (85,449,277 bytes). 1 photograph digitized from original negative. 2400 DPI TIF. 300 DPI 4x6 JPG.
Keywords: Electronic records; Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)